Productive art engagement in a hybrid format: effects on emotions of older adults during COVID-19 pandemic - Payne, Magali; Galery, Kevin; Plonka, Alexandra; Lemaire, Justine; Derreumaux, Alexandre; Fabre, Roxane; Mouton, Aurélie; Sacco, Guillaume; Guerin, Olivier; Manera, Valeria; Robert, Philippe; Beauchet, Olivier; et al. (Frontiers in Public Health, 2024)
Introduction: Previous studies have shown benefits of productive art-activity on frail older adults’ mental and physical health. In this study we investigated the effects of art-producing activities in a hybrid format (in-person and online) in a context of lockdown compared to previous studies taking place in museums, and their effects on wellbeing, quality of life, physical frailty and apathy in older adults. Methods: We conducted a randomized unicentric control trial on a sample of 126 seniors older than 65 years (mean age 71.9 ± 2.3, 81% female) living in Nice (France). Participants were randomized in two parallel groups (intervention group with n=62 vs control group with n=64) conducted during pandemic, between March and May 2021. The intervention group involved participatory art-based activities conducted in a hybrid format, either in-person or online once a week for 2 hours over a 12-week period.. No specific intervention was proposed to the control group. The main aim was to evaluate how this hybrid format would impact the well-being, the quality of life, and the physical frailty of participants. The secondary aim was to compare our results to the previous studies conducted by Beauchet and colleagues, and the third aim was to evaluate the impact of the intervention on apathy. Validated scales were implemented in RedCap and administered at baseline (M0) and at the end of the third month (M3). Results: The intervention group showed significant improvement in their quality of life (p = 0.017) and their level of apathy (p = 0.016) after intervention. Emotional blunting increased significantly in the control group (p = 0.016) while it remained stable in the intervention group. No significant improvement was observed on the frailty, and wellbeing scores remained constant in both groups. Conclusion: This randomized control trial confirmed emotional effects in seniors practicing an art-based activity in a hybrid format during pandemic, on a weekly basis for 3 months. Trial registration: Clinical Trial Number: NCT04570813. Title: ART&Santé : Effets d’ateliers artistiques et participatifs au MAMAC de Nice Sur la santé des seniors; September 19, 2020.